2015
DOI: 10.17265/2161-6264/2015.03b.002
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effect Investigation toward Peat Surface CO2 Emissions by Planting Leguminous Cover Crops in Oil Palm Plantations in West Kalimantan

Abstract: Abstract:The aim of this research was to know the impact of planting leguminous cover crops (LCCs) of Mucuna bracteata and Calopogonium mucunoides in oil palm plantation on peatland on reducing CO 2 emissions. Atmosphere temperature, peat surface temperature, in-closed chamber temperature and peat surface CO 2 fluxes were monitored on two adjacent experimental plots. The first experimental plot was on the newly opened peat surface (NOPS) and another was on the eight years planted oil palm land (EPOL). The clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In contrast, in Sabaju the harvest path had significantly higher R tot than the frond pile and cover plants. These differences in R tot among microforms are noteworthy because few other studies consider the effects of surface management practices on R tot , with the exception of work by Arifin et al (2015), who also found that R tot was significantly lower when measured from beneath cover plants than from the harvest path. These differences in R tot among microforms are significant because they have direct bearing not only predicting and upscaling land-atmosphere fluxes, but also because they provide insight into how soil surface management practices are affecting soil CO 2 and CH 4 dynamics.…”
Section: Carbon Fluxes Vary Spatially In Managed Tropical Peatlandsmentioning
confidence: 89%
“…In contrast, in Sabaju the harvest path had significantly higher R tot than the frond pile and cover plants. These differences in R tot among microforms are noteworthy because few other studies consider the effects of surface management practices on R tot , with the exception of work by Arifin et al (2015), who also found that R tot was significantly lower when measured from beneath cover plants than from the harvest path. These differences in R tot among microforms are significant because they have direct bearing not only predicting and upscaling land-atmosphere fluxes, but also because they provide insight into how soil surface management practices are affecting soil CO 2 and CH 4 dynamics.…”
Section: Carbon Fluxes Vary Spatially In Managed Tropical Peatlandsmentioning
confidence: 89%
“…Presence of understory vegetation, including cover crops such as nitrogen-fixing Mucuna bracteata which are commonly planted in young plantations, can help reduce soil erosion, and increase soil fertility and water-holding capacity (Corley and Tinker, 2003a;Baligar and Fageria, 2007;Anderson, 2008). Cover crops can help to reduce soil temperature which, particularly in peat soils, can help to reduce the rate of microbial oxidation, thereby reducing CO 2 emissions (Arifin et al, 2015). Cover crops can also help to reduce access of rhinoceros beetles (Oryctes rhinoceros, a pest species of young palms) to rotting logs that they use for breeding (Bedford, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Similar marginal effects were shown by the distance from the oil palm tree on N prediction in the OP site (Figures 6 and 7). The BMP management allowed the fast-growing weeds (Ashton-Butt et al, 2018;Luke et al, 2019;Rahman et al, 2021) or leguminous plants (Arifin et al, 2015;Agus et al, 2019) to occupy the interrow and frond stack as understory cover crops/UCC. N mineralization derived from UCC's litter decomposition could enhance N in peat outside of the fertilization circle, hence, minimizing the effect of distance.…”
Section: Discussionmentioning
confidence: 99%